Managing legal change initiatives. (2021) - McKenna, Patrick J; Marson, Nick; Greene, Arthur G; Dr, Murray, Dr Bob; Hedley, Andrew; East, Neryl; Hart, Duncan; Dr, Fortinberry, Dr Alicia; Parnell, David J; Mynott, Carol
No abstract available